Design of a Compact Passband Frequency Selective Surface with Stable Resonance. (11th July 2017) - Peddakrishna, Samineni; Khan, Taimoor; Kanaujia, Binod Kumar; Nasimuddin, N.
Abstract : We propose a compact planar passband frequency selective surface (FSS) operating at the resonance frequency of 3.81 GHz. The proposed FSS is composed of single layer of the Archimedean spiral type with the interdigital capacitance between the corners of metallic patches printed on one side of the substrate. Compared to the operating wavelength, the size of the proposed single layer FSS is 0.066λ 0 (λ 0 is the free space wavelength at 3.81 GHz). The performance such as transmission and reflection coefficient of the proposed FSS demonstrates excellent resonance stability for different polarization and different incident angles. Finally, the optimized simulated results are validated with measured results by a fabricated prototype of 31 × 31 array elements on 170 × 170  mm 2 substrate area.